2014
DOI: 10.1123/pes.2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Training on Heart Rate Variability in Healthy Children: A Systematic Review With Meta-Analysis

Abstract: The positive effects of physical training on heart rate variability (HRV) in healthy adults are widely recognized; however, the responsiveness to training in healthy children has not yet been established. The aim of this study was to determine the influence of physical training on HRV in prepubertal healthy children. Systematic computerized searches were performed from 1950 to 2012 in the following databases: Medline, Embase, Cinahl, Lilacs, Scielo, SportDiscus, ProQuest; Web of Science; PEDro; Academic Search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…In studies on healthy subjects, exercise did not have any significant effect on the HF (log) value14, 15 ) . However, in studies on patients receiving rehabilitation because of chronic obstructive pulmonary disease or myocardial infarction, elderly people, obese adolescents, and those in high-stress occupations, exercise has a statistically significant effect on the HF (log) value, similar to this study7,8,9, 11,12,13 ) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In studies on healthy subjects, exercise did not have any significant effect on the HF (log) value14, 15 ) . However, in studies on patients receiving rehabilitation because of chronic obstructive pulmonary disease or myocardial infarction, elderly people, obese adolescents, and those in high-stress occupations, exercise has a statistically significant effect on the HF (log) value, similar to this study7,8,9, 11,12,13 ) .…”
Section: Discussionmentioning
confidence: 96%
“…However, in studies on healthy subjects and those with fibromyalgia, exercise did not have a statistically significant effect on HRV14, 15 ) . In studies where only strengthening exercise was done, without any aerobic exercise that can increase heart rate, or in studies where exercise duration was 8 weeks or shorter, exercise did not have any effect on HRV16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, a task force 31 specified standards for calculating PRV measures and reporting results, which have been considered in the present study. Accuracy of the ECG has since then been investigated in numerous studies in health and disease, [1][2][3][4] and the correlation with both PRV PPG 7 and PRV NIRS 25 under resting conditions has been reported to be high.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of HRV as a tool for basic research as well as for medical diagnostic purposes to assess the function of the autonomic nervous system has been verified in numerous studies. [1][2][3][4] The gold standard is the analysis of interbeat (RR) intervals derived from electrocardiography (ECG). Alternatively, pulse cycle intervals variability based on blood flow pulsations (i.e., PRV) can be derived from pulse oximetry, i.e., photoplethysmography (PPG) (PRV PPG ).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of randomized controlled trials in healthy children, da Silva et al [5] found no effect of exercise training on HRV. Blom et al (2009) [1] found, when studying a group of healthy adolescents, that their HRV was related to their self-reported physical activity.…”
Section: Introductionmentioning
confidence: 99%